PEMBERDAYAAN MASYARAKAT DALAM MENGURANGI DAMPAK KEBISINGAN DAN KARBON KENDARAAN BERMOTOR - Amanda Aulia; Ramadhani Fitri; Mhd Furqon (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity aims to increase public understanding of how to reduce the impact of noise and carbon emissions from motor vehicles. Noise and carbon emissions from motor vehicles are environmental problems that are increasing along with the growth in the number of vehicles in urban and rural areas. These impacts not only affect air quality, but also the physical and psychological health of the community. This community service activity aims to empower the community in reducing the impact of noise and carbon emissions from motor vehicles through education, training, and concrete actions based on community participation. The implementation methods include socialization of the impacts of noise and emissions, training on environmentally friendly vehicle maintenance, and campaigns promoting the use of alternative modes of transportation such as bicycles, walking, or public transportation. The results of the activity showed an increase in community knowledge and awareness of environmental issues and the formation of self-help groups that play an active role in campaigning for environmentally friendly behavior. With this program, the community is able to contribute to reducing noise and air pollution, while supporting the creation of a healthier and more sustainable environment.